Reviewing Identification and Intervention of School Bullying on Perception of Middle School Counselling Teacher on Dealing Bullying - Lia Endriyani; Nindita Kumalawati Santoso (Alma Ata University Press, 2020)
Bullying behavior is serious problem that can affect mental and psychosocial development in both the bully and the victim. School bullying happens in school aged children and occurs during or after school hours. As bullying happened in schools, counseling teacher is one of main resource in efforts to prevent and to intervene bullying situations. Counseling teacher has competencies and authorities regarding this matter. This study aimed to know perception of counseling teacher on dealing with bullying by reviewing information about identification and intervention of school bullying. This study was quasy experiment with one group pre-test and post-test design. Purposive sampling was used to obtain 16 middle school counseling teachers in Kasihan and Pajangan sub district as participants to join this study. The data were collected through modification of Perceptions of Bullying Questionnaire and The Handling Bullying Questionnaire. Data were analyzed by Paired t-test. Majority of respondents were more than 46 years with the highest level of education was bachelor degree. Counseling teacher had experience as counselling teacher for more than 10 years. Teacher’s perceived ability to identify the bully and the victim was in “enough” category. Perceived method to deal with the bully was involving students and their parents while method to deal with the victim was involving students, parents and school personnel. There are significant differences of teacher’s perception on handling bullying before and after intervention (p- value=0.032). Giving information can give a positive effect against the perception the guidance counselor in dealing with bullying.